Effects of virtual reality use in children aged 10 to 12 years - Silva, Karol; Breeland, Nichole; Clark, Ashley M.; Öztekin, Ilke; Kelly, Rachel L. (Frontiers in Virtual Reality, 2025)
Virtual Reality (VR) technologies allow children to experience a multitude of environments and interactions; however, little is known regarding the extent to which moderate and sustained VR use impacts aspects of children’s physical and cognitive functioning. In the present research, we examine the extent to which 60-min VR play sessions over the course of 4 days impact 10- to 12-year-olds’ visual functioning (e.g., acuity, stereoacuity), visuomotor coordination (e.g., hand-eye coordination), postural stability, inhibitory control, and subjective visual and musculoskeletal discomfort (e.g., symptoms of visually-induced motion sickness). Measures of visual, physical, and cognitive functioning were administered before any VR use (day 1), after 4 days of daily VR use (day 4), and after a break from VR use (day 5). Results from this 5-day study demonstrate that moderate and daily VR usage did not negatively affect children’s visual, physical, and cognitive functioning. Overall, the present study provides novel insights into the growing body of evidence regarding the health and safety considerations surrounding VR use by children.